Kajian Kuat Tarik Belah pada Beton Variasi Limbah Granit Sebagai Substitusi Parsial Agregat Kasar - Diajeng Derrissyifa Salvia; Wibowo Wibowo; Endah Safitri (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The development of concrete making technology has developed rapidly nowdays, the innovations in terms of material use and workmanship. The implementation of construction work carried out today pays attention to aspects of strength, rigidity, and high durability, as well as sustainability. To support these two things, research can be carried out on making concrete using granite waste. The research method used in this study is an experimental method. The concrete mix design uses variations of granite waste with successive levels of 0%, 15%, 30%, and 45%. The test specimen used for tensile strength testing is cylindrical with a diameter of 15 cm and a height of 30 cm, the test uses 12 specimens where each variation uses 3 specimens. The test is performed when the specimen has reached the age of 28 days. The test specimen tested has met the planned compressive strength requirements at a concrete life of 28 days where the results are greater than 20 MPa. Results of testing the tensile strength of concrete variations of granite waste as a partial substitution of coarse aggregate with variations of granite waste of 0%, 15%, 30%, and 45% respectively; 2.43 MPa; 2.50 MPa; 2.97 MPa; and 2.78 MPa.